EDUKASI TOILET TRAINING UNTUK MELATIH KEMANDIRIAN ANAK - Anjar Nurrohmah; Tri Susilowati (P3M Universitas Aisyiyah Surakarta, 2021)
One of the problems that exist in toddlers is wetting and depending on parents for toileting activities. If not resolved early on, the child will not be independent, less confident and shy. Parents as the closest caregivers of children have an important role in teaching their children. The purpose of this activity is to increase parents' knowledge about how to teach toilet training to children. The activity was carried out at the Posyandu Subur X, Sidodadi, Masaran, Sragen. The method used in this activity is discussion and education, with a pre-test and a post-test. This activity was attended by 23 participants who have toddlers, visited the Posyandu and were willing to become participants. The knowledge how to teach toilet training before given education was sufficient, as many as 11 people (48%). While the knowledge of respondents after given education was mostly good, as many as 19 people (83%). Based on this, it can be concluded that the education method is effective in increasing respondents' knowledge about how to teach toilet training to children.Â Â